Алгоритм розрахунку перехідних і усталених процесів асинхронного мотора - Чабан, В.Й.; Гоголь, З.І.; Костючко, С.М. (Електротехніка і електромеханіка, 2011)
The paper introduces a calculation algorithm for transient and steady-state processes in a three phase induction motor with a capacitor in one of the stator phases. Differential equations are given in normal Cauchy form. The transient process occurs under given initial conditions, while the steady-state process takes place under such initial conditions that eliminate the transient response. Simulation results are given.